Online peer-tutoring: a renewed impetus for autonomous English learning - Luis Ignacio Herrera Bohórquez; José David Largo Rodríguez; John Jairo Viáfara González (HOW)
Challenges to an existing face-to-face peer-tutoring model grew into an opportunity to integrate online technologies as a support for English autonomous learning in two undergraduate teacher education programs at a Colombian public university. This qualitative study examines how a group of tutees’ exposure to an online-based peer-tutoring model shapes their autonomy. Informed by data from questionnaires, a focus group interview, tutees’ logs, and records of their engagement with the model’s internet resources, researchers identified a change in participants’ conceptualization of autonomous learning and an impact on their self-directed practices rooted in the immediacy, accessibility, comfort and availability of resources that the online peer-tutoring model favors.